flexible contexts and context reduction

Claus Reinke claus.reinke at talk21.com
Thu Mar 27 08:25:13 EDT 2008


perhaps i'm missing something but, instead of trying to deduce
conditions from conclusions, why can't you just follow ghc's
suggestion, and add the constraints to the constructor?

data Foo a where
   Foo1 :: a -> Foo a
   Foo2 :: (Ord a,Ord b) => Foo a -> Foo b -> Foo (a, b)

(possibly with another constraint on Foo1)

claus

> A closer example to what I was actually doing was this:
> 
> {-# LANGUAGE GADTs #-}
> module Foo where
> 
> data Foo a where
>   Foo1 :: a -> Foo a
>   Foo2 :: Foo a -> Foo b -> Foo (a, b)
> 
> unFoo :: Ord a => Foo a -> a
> unFoo (Foo1 a) = a
> unFoo (Foo2 x y) = (unFoo x, unFoo y)
> 
> [in the real code I did actually use the Ord constraint in the base case]
> 
> The error I get is this:
> 
> Foo.hs:10:20:
>    Could not deduce (Ord a2) from the context ()
>      arising from a use of `unFoo' at Foo.hs:10:20-26
>    Possible fix: add (Ord a2) to the context of the constructor `Foo2'
>    In the expression: unFoo x
>    In the expression: (unFoo x, unFoo y)
>    In the definition of `unFoo': unFoo (Foo2 x y) = (unFoo x, unFoo y)
> 
> Foo.hs:10:29:
>    Could not deduce (Ord b1) from the context ()
>      arising from a use of `unFoo' at Foo.hs:10:29-35
>    Possible fix: add (Ord b1) to the context of the constructor `Foo2'
>    In the expression: unFoo y
>    In the expression: (unFoo x, unFoo y)
>    In the definition of `unFoo': unFoo (Foo2 x y) = (unFoo x, unFoo y)
> 
> Which suggests that GHC has also lost track of the fact that Ord (a, b) is true. But 
> it would certainly be necessary to get from Ord (a, b) to (Ord a, Ord b) to get that
> to work.



More information about the Glasgow-haskell-users mailing list